European Small Business Finance Outlook - Roger Kelly; Helmut Kraemer-Eis (European Investment Fund (EIF), 2011)
This analysis provides an overview of the main markets relevant to EIF. We start by discussing the general market environment, then look at the main aspects of equity finance and the SME Securitisation market. Finally, we briefly highlight important aspects of microfinance in Europe.
Keywords: 330